The Attempts of Pro-Social Communication Agents in Communicating and Shaping Environmental Behaviour via the Internet - Bailey, James A (2009)
With the increase in focus on environmental advertising during the early 1990s, it is surprising that more research has not focused on advertisings effect on influencing and shaping consumer behaviour change. This is seen as crucial in the next few decreased due to a general agreement on the effect that consumers behaviours have on climate change. Communicating this pro-social behaviour change has in recent years diversified into Internet communications and other communication agents, as well as traditional behaviour change influencers such as the government, have emerged. This study reviews using a content analysis approach, the ways in which communications agents adopt social marketing strategies (to shape behaviour change) through Internet communications (specifically their websites), the overall attempt used and the perceived view of the general Internet communications environment for environmental behaviour change.